Działalność kościelna arcybiskupa gnieźnieńskiego Andrzeja Olszowskiego: Church activity of Andrzej Olszowski the archbishop of Gniezno - Wilk-Woś, Zofia (Prace Polonistyczne, 2019)
The objective of this article is to present ecclesiastic activity of the Archbishop of Gniezno and Primate Andrzej Olszowski in light of the few source materials preserved in the Archdiocese Archives in Gniezno. As the Primate and the first Senator of the Republic of Poland, Olszowski did not avoid criticism for his political activities. Nevertheless his church activity was assessed positively, although due to his public involvement he had little time to fully engage in ministerial service in his subsequent dioceses.